2013
DOI: 10.5861/ijrsll.2013.212
|View full text |Cite
|
Sign up to set email alerts
|

A review of language teacher selection examination and recruitment in Turkey and Poland

Abstract: This paper presents a review of language teacher selection examination and recruitment in Turkey and Poland, together with the national assessments conducted to assess candidates entering the teaching profession such as Praxis I and II and the Teaching Knowledge Test. It further discusses KPSS (Selection Examination for Professional Posts in Public Organizations) conducted and used as the selection process for teaching positions in the state schools in Turkey and compares it with the examinations discussed abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Previous research on SKT has mainly focused on suggestions on the examination process and the implications of SKT takers with this respect. Kılıçkaya and Krajka (2013) reviewed language teacher selection examination and recruitment in Turkey and Poland and argued that in Turkey a reliable and valid examination should be implemented which measures the subject knowledge of exam takers, and in Poland a recruitment process based on objective criteria should be enacted rather than local prerequisites. Studies conducted on preschool prospective teachers showed the importance of SKT; however, they also reflected that a more comprehensive content should be included in by considering various factors (Recepoğlu, et al, 2016;Çelik, 2016;Halmatov & Kızıltaş, 2019).…”
Section: Con T Ent An Al Ys Is Of Th E Old An D N Ew D Ist Ribut Io N Of the T Op Ics In Skt For Elt Pros P Ect Iv E T Ea Chersmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on SKT has mainly focused on suggestions on the examination process and the implications of SKT takers with this respect. Kılıçkaya and Krajka (2013) reviewed language teacher selection examination and recruitment in Turkey and Poland and argued that in Turkey a reliable and valid examination should be implemented which measures the subject knowledge of exam takers, and in Poland a recruitment process based on objective criteria should be enacted rather than local prerequisites. Studies conducted on preschool prospective teachers showed the importance of SKT; however, they also reflected that a more comprehensive content should be included in by considering various factors (Recepoğlu, et al, 2016;Çelik, 2016;Halmatov & Kızıltaş, 2019).…”
Section: Con T Ent An Al Ys Is Of Th E Old An D N Ew D Ist Ribut Io N Of the T Op Ics In Skt For Elt Pros P Ect Iv E T Ea Chersmentioning
confidence: 99%
“…To achieve this goal, Klassen et al (2020) propose that SKT is a very significant progressional examination for prospective teachers since it helps them to annihilate some unexpected difficulties they may face later on in their professional lives. Therefore, the selection and recruiting process of these teachers necessitates a reliable and valid examination (Kılıçkaya & Krajka, 2013) for prospective teachers. Taking into consideration this relevance, this study aimed to reflect prospective ELT Teachers' conceptions and suggestions on the new distribution of the subjects and topics in SKT with a systematic investigation that has not been previously investigated in this field.…”
Section: Con T Ent An Al Ys Is Of Th E Old An D N Ew D Ist Ribut Io N Of the T Op Ics In Skt For Elt Pros P Ect Iv E T Ea Chersmentioning
confidence: 99%
“…Aynı zamanda öğretmen açığı olan bazı alanlarda çok düşük puanla atamalar gerçekleşirken, öğretmen fazlası olan alanlarda çok yüksek puanlı öğretmenler istihdam edilememektedir. Bu durum, sınavın amacı olan öğretmenlik yeterliliklerini sağlayan nitelikteki bireyleri belirlemekte sorun yaratmaktadır (Kılıçkaya & Krajka, 2013).…”
Section: Introductionunclassified